Quantitative Characterization of Arnicae flos by RP-HPLC-UV and NIR Spectroscopy - Ivanova, Daniela (Foods, 2018)
The possibility of applying near-infrared (NIR) spectroscopy to monitor 13 active components (phenolic acids, flavonoids, and sesquiterpene lactones) in Arnicae flos was studied. The preprocessing of the spectra were performed by using the conventional Golay-Savitzky procedure and the newly developed step-by-step filter. The results obtained show that the step-by-step filter derivatives provide a better signal-to-noise ratio at a lower convolution window. Better calibration for the content of protocatechuic acid, chlorogenic acid, caffeic acid, p-cumaric acid, ferulic acid, isoquercitrin, and quercetin were obtained by step-by-step filter derivatives, compared to the direct raw spectra processing and the Golay-Savitzky approach. Although the step-by-step filter substantially reduces the spectral distortion, the convolution procedure leads to loss of spectral points in the red end of the spectral curve. Probably for this reason this approach shows better calibration only in seven of the monitored 13 active components.